Contraceptive Prevalence and Pattern Amongst Human Immunodeficiency Virus infected (HIV) Women of Reproductive Age Attending the Special Treatment Clinic (STC) of a Tertiary Health Facility in North Central Nigeria - Ikenna, Chima; Baamlong, Nicholas; Blessing, Akor; Rebecca, Ripiye; Abubakar, Haruna; Rukayat, Abdulkareem; Joel, Abu; Godiya, Bwala (British Journal of Healthcare and Medical Research, 2024)
Background: Nigeria has the second largest burden of HIV in the world and Mother to Child transmission of HIV is the predominant mode of transmission in children. Family planning is the most cost-effective strategy to reduce mother to child transmission of HIV. Aim/Objective: The study was to determine the prevalence and pattern of contraceptive use amongst HIV infected women attending the special treatment clinic of University of Abuja Teaching Hospital. Methods: A cross-sectional descriptive study was carried out on 383 enrolled participants using systematic random sampling technique. Data was collected via a pretested semi structured interviewer administered questionnaire. Results: The contraceptive prevalence among all study participants was 47% while the prevalence of contraceptive use among the sexually active study participants was 64.1%. The most commonly used contraceptive was the male condom (66.1%). The practice of dual contraception among participants who used any form of contraceptive was 25.4% and the commonest combination was condom with oral contraceptive pill. Conclusion: Despite the strides made so far in family planning services among HIV infected women there is still a gap in the reproductive health of these women as 35.9% of study participants did not practice any form of contraception while only 25.4% use dual contraception.